2012
DOI: 10.1007/s10059-012-2188-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis Dehydration- Responsive Element-Binding Protein 2C Confers Tolerance to Oxidative Stress

Abstract: Dehydration-responsive element-binding proteins (DREBs) regulate plant responses to environmental stresses. In the current study, transcription of DREB2C, a class 2 Arabidopsis DREB, was induced by a superoxide anion propagator, methyl viologen (MV). The oxidative stress tolerance of DREB2C-overexpressing transgenic plants was significantly greater than that of wild-type plants, as measured by ion leakage and chlorophyll fluorescence under light conditions. The transcriptional activity of several ascorbate per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 28 publications
1
36
1
1
Order By: Relevance
“…A study of Hsf1's action on the circadian clock in mammalian cells was reported recently; however, the molecular mechanism remains unknown (44,45). In general, Hsfs have been described to target HSP genes via multiple HSE repeats in their promoters, and few studies exist where Hsfs regulate non-HSP genes (46)(47)(48). Importantly, mammalian Hsfs are known to control the expression of various developmental genes in addition to HSPs, and it recently has become clear that the stress-independent expression of HSF1 is crucial in oncogenesis (49, 50).…”
Section: Discussionmentioning
confidence: 99%
“…A study of Hsf1's action on the circadian clock in mammalian cells was reported recently; however, the molecular mechanism remains unknown (44,45). In general, Hsfs have been described to target HSP genes via multiple HSE repeats in their promoters, and few studies exist where Hsfs regulate non-HSP genes (46)(47)(48). Importantly, mammalian Hsfs are known to control the expression of various developmental genes in addition to HSPs, and it recently has become clear that the stress-independent expression of HSF1 is crucial in oncogenesis (49, 50).…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al (2012) also reported that DREB2C plays an important role in promoting oxidative stress tolerance in Arabidopsis.…”
Section: Introductionmentioning
confidence: 93%
“…Among others, we observe misregulation of RING MEMBRANE-ANCHOR 1 (RMA1), an uncharacterized protein with possible E3 ubiquitin ligase activity, and DREB2C, a member of the DREB subfamily A-2 of the ERF/ AP2 transcription factor family implicated in drought stress responses (Fig. 4 B-E) (46)(47)(48)(49). Interestingly, in addition to DREB2C, 39 other transcription factors identified as CCA1 targets in this study recently have been shown to interact with the CCA1 promoter in a yeast one-hybrid assay (Dataset S3) (50).…”
Section: Countmentioning
confidence: 99%